Independência para realização de atividades de vida diária e sua relação com o nível de severidade em indivíduos pós-acidente vascular cerebral: um estudo longitudinal - Ludmilla Ribeiro Batista (2022)
Stroke is the second leading cause of death and disability in adult life. For individuals who survive a stroke, the limitation in their ability to perform activities of daily living may begin at hospital admission and persist for years after the event. Although the recovery of the ability to perform post-stroke activities of daily living has been described in previous studies, the isolated analysis of each activity of daily living is incipient. Furthermore, the influence of the stroke severity level, assessed during hospitalization, on the transition from dependence to independence in individual activities of daily living in the acute and subacute phases of post-stroke evolution, which correspond to the period of great potential for rehabilitation functional, has not yet been analyzed. Understanding the influence of the stroke severity level on the recovery of the ability to perform different activities of daily living in post-stroke individuals can contribute to the definition of specific, realistic, achievable and measurable goals, directing professionals in clinical decision-making, in the identification of individuals with better or worse prognosis for recovery of functional capacity, even in the hospital context. In this sense, the objectives of this study were: i) identify the level of dependence and independence to carry out activities of daily living, analyzed by the items of the Modified Barthel Indicator (MBI), in hospitalization (T1), three (T2) and six months (T3) post-stroke; and ii) to examine the association between the level of stroke severity, assessed using the National Institutes of Health Stroke Scale (NIHSS) during hospitalization, and the recovery of the ability to perform activities of daily living at three and six months after-stroke. To this end, a prospective cohort observational study was carried out, conducted following the methodology proposed by international guidelines (CAAE: 84263818.8.0000.5149). The final sample consisted of 180 individuals, with a mean age of 61±15 years, 55% of whom were women and 86% had a diagnosis of ischemic stroke. The binary categorical dependent variables were the MBI items. The independent variable was the level of stroke severity, assessed during hospitalization using the NIHSS, considering binary categorical values. The MBI has 10 items, thus building 10 models to assess the changing participants between dependence or independence over the three assessments (T1, T2 and T3), as well as the influence of the stroke severity level on this transition. To analyze the relationship between the ability to perform activities of daily living during hospitalization, three and six months after the stroke and the level of stroke severity, the Generalized Estimating Equations (GEE) method was used. In each model, the odd ratio and the standard error were calculated, used to construct the 95% confidence intervals. In the first six months after the stroke, recovery of the ability to perform activities of daily living was observed, especially between discharge from the stroke unit and three months after the stroke. Individuals with moderate/severe involvement were more likely to remain dependent for activities such as eating (OR=1.27; CI 95%=1.03-1.55), bathing (OR=1.30; CI 95%= 1.11-1.50), dressing (OR=1.19; CI 95%=1.04-1.36), transfer (OR=1.24; CI 95%=1.05-1.46) , stairs (OR=1.46; CI 95%=1.27-1.66) and ambulation (OR=1.21; CI 95%=1.02-1.43). The results showed that stroke severity, assessed in the first post-stroke hours during hospitalization using the NIHSS, was associated with the transition between dependence/independence in six of the ten activities analyzed. Understanding the functional recovery trajectory of each activity and the influence of the stroke severity level on the transition from dependence to independence in each activity may help the rehabilitation team and the patient in defining realistic goals, as well as enabling prior planning resources needed for care after hospital discharge.